Screening for Predictive Parameters Requiring Psycho-Oncological Intervention via the National Comprehensive Cancer Network Distress Thermometer in the Follow-Up of Uveal Melanoma Patients - Klingenstein A (Dove Medical Press, 2020)
Annemarie Klingenstein,1 Christina Samel,2 Aylin Garip-Kuebler,1 Siegfried G Priglinger,1 Paul I Foerster1 1Department of Ophthalmology, Ludwig-Maximilians-University, Munich, Germany; 2Institute of Medical Statistics and Computational Biology, Faculty of Medicine, University of Cologne, Cologne, GermanyCorrespondence: Annemarie KlingensteinDepartment of Ophthalmology, Ludwig-Maximilians-University, Klinikum der Universität München, Campus Innenstadt, Mathildenstraße 8, Munich D-80336, GermanyTel +49 89 44005 3811Fax +49 89 44005 5160Email Annemarie.Klingenstein@med.uni-muenchen.deAim: To assess a profile of uveal melanoma patients at risk of requiring active psycho-oncological intervention by employing the National Comprehensive Cancer Network (NCCN) distress thermometer.Methods: Multivariate correlation and multiple linear regression analysis of data collected retrospectively from 106 consecutive patients suffering from uveal melanoma.Results: Distress levels correlated with practical (p = 0.01), emotional (p = 0.003) and physical problems (p = 0.001) as well as the total number of issues reported (p < 0.001; ANOVA, respectively). Emotional issues added up to 39% of influence on distress levels. Nervousness, worry and sadness as the most important emotional issues tested correlated significantly with anatomic stage, tumor T-category, metastatic status and time after primary diagnosis and were present more frequently in patients with higher distress levels (p < 0.001, p = 0.002, p = 0.004, respectively, Fisher’s exact test). Pre-existing psycho-oncological support was more frequent in metastatic patients and patients with higher anatomic stage tumors (p = 0.008 and p = 0.003; Fisher’s exact test).Conclusion: The distress thermometer proved to be useful for rapid assessment of patients requiring active intervention. A higher number of distress items recorded correlated with elevated distress levels. Emotional issues were responsible for the majority of problems. A typical patient profile at risk of developing distress requiring close attention of caregivers includes high anatomic stage, high T-category, presence of metastases and early follow-up. Correct diagnosis and interpretation of distress-levels should help improve the quality of life of uveal melanoma survivors.Trial Registration: Not applicable.Keywords: quality of life, NCCN distress thermometer, uveal melanoma, psycho-oncological distress, cancer